Marketing Strategy at Middle Star Hotels in Makassar City - Rezky Amalia Hamka; Sutrisno Sutrisno; Arwin Arwin (CV. Sakura Digital Nusantara, 2023)
This study aim For analyze the marketing strategy implemented by the Middle Star Hotels in face competition. This study is study qualitative in nature descriptive. Population in this study is internal and external parties external from Middle Star Hotels, meanwhile informant study this is Sales Executive, Senior Human Resource Office, and two Customers. Data collection techniques are carried out with technique observation and interview. Data analysis technique used is SWOT analysis, that is something tool analysis used for formulate a strategy or identification various factor strategic based on internal factors as well external. This study results show that position on the Cartecius Diagram appear that Middle Star Hotels located in cell I with use an aggressive strategy, with a winning strategy cost, with give cheap price, so increase power buy consumer, this show that Middle Star Hotels face a number of opportunity and have various propelling force for get opportunities. Meanwhile, the position of Middle Star Hotels on the internal external matrix is also in cell I, namely position grow and develop or is in integration vertical which is position very competitive market in business powerful hospitality competitive tall between star hotels three other.